GRINGSING ETHNOSCIENCE: STRUCTURAL HOMOLOGY AND BALI AGA IDENTITY IN TENGANAN PEGRINGSINGAN - I Nengah Juliawan; I Kadek Edi Palguna; I Kadek Abdhi Yasa; Kadek Anggie Noviari Dewi (Institut Seni Indonesia Denpasar, 2025)
This study analyzes the integrated ethnoscience system of the Wayang patterned Gringsing cloth, examining its role as an active agent in rituals, and understanding its function as a marker of cultural identity for the Bali Aga Tenganan Pegringsingan community. Qualitative-ethnographic research in Tenganan Pegringsingan, Bali. Data collection techniques: in-depth interviews, participant observation in the Usaba Sambah ritual, and analysis of awig-awig documents. Data analysis techniques: Miles and Huberman's model, Spradley's ethnographic analysis. Theoretical framing: ethnoscience, cultural semiotics, and structuralism. Gringsing is a woven codex that integrates ethno-chemistry (overdyeing as Rwa Bhineda) and ethno-technology. This cloth functions as spiritual armor during liminal rites of passage and a portable constitution that replicates the Tri Mandala. Structural homologies are found that connect the logic of purity in the domains of cloth, body (endogamy), and law (awig-awig). This study introduces productive inefficiency (slowdown as resistance) and structural homology as theoretical frameworks. Practically, this study identifies a controlled commodification model in which Geographical Indications (GI) are used as a defensive shield, leveraging market value to address the artisan regeneration crisis.